Transcriptomic Complexity in Strawberry Fruit Development and Maturation Revealed by Nanopore Sequencing - Chen, Qing; Lin, Ximeng; Tang, Wenlu; Deng, Qian; Wang, Yan; Lin, Yuanxiu; He, Wen; Zhang, Yunting; Li, Mengyao; Luo, Ya; Zhang, Yong; Wang, Xiaorong; et al. (Frontiers in Plant Science, 2022)
The use of alternative transcription start or termination sites (aTSS or aTTS) as well as alternative splicing (AS) produce diverse transcript isoforms, playing indispensable roles in the plant development and environmental adaptations. Despite the advances in the finding of the genome-wide alternatively spliced genes in strawberry, it remains unexplored how AS responds to the developmental cues and what relevance do these outcomes have to the gene function. In this study, we have systematically investigated the transcriptome complexity using long-read Oxford Nanopore Technologies along the four successive developmental stages. The full-length cDNA sequencing results unraveled thousands of previously unexplored transcript isoforms raised from aTSS, aTTS and AS. The relative contributions of these three processes to the complexity of strawberry fruit transcripts were compared. The aTSS and aTTS were more abundant than the AS. Differentially expressed transcripts unrevealed the key transitional role of the white fruit stage. Isoform switches of transcripts from 757 genes were observed. They were associated with protein-coding potential change and domain gain or loss as the main consequences. Those genes with switched isoforms take part in the key processes of maturation in the late stages. A case study using yeast two hybrid analysis supported the functional divergence of the two isoforms of the B-box protein 22. Our results provided a new comprehensive overview of the dynamic transcriptomic landscape during strawberry fruit development and maturation.